Reaction-diffusion in the NEURON simulator - McDougal, Robert A.; Hines, Michael L.; Lytton, William W. (Frontiers in Neuroinformatics, 2013)
In order to support research on the role of cell biological principles (genomics, proteomics, signaling cascades and reaction dynamics) on the dynamics of neuronal response in health and disease, NEURON has developed a Reaction-Diffusion (rxd) module in Python which provides specification and simulation for these dynamics, coupled with the electrophysiological dynamics of the cell membrane. Arithmetic operations on species and parameters are overloaded, allowing arbitrary reaction formulas to be specified using Python syntax. These expressions are then transparently compiled into bytecode that uses NumPy for fast vectorized calculations. At each time step, rxd combines NEURON's integrators with SciPy’s sparse linear algebra library.